• Support PF! Buy your school textbooks, materials and every day products Here!

Solving for variables

  • Thread starter marissa12
  • Start date
  • #1
11
0
a particle of mass m moving in the x direction at constant acceleration a . During a certain interval of time, the particle accelerates from v_initial to vfinal , undergoing displacement s given by s=x_final-x_initial.

Express the acceleration in terms of v_initial, v_final, and s:
that was easy.. i got

a=(v_final-v_initial)/(s/((v_initial+v_final)/2))

since F=ma
W=F*s

the question is Give an expression for the work in terms of m, v_initial, v_final ?

and i cant seem to eliminate the 's' because i end up getting

W=m*a(see above) *s and i cant get eliminate it? any ideas?
 

Answers and Replies

  • #2
11
0
the 2nd part of the problem is w= intergral of { mv*dv} between v_final and v_initial
and we are supposed to express that in m_vinitial and v_final

and i got the answer ((m*v_final)^2-(m*v_initial)^2)/2 and that didnt work. i used the basic intergral formula

fint{t*dt between a and b} = b^2-a^2/t
 
  • #3
Fermat
Homework Helper
872
1
marissa12 said:
...
the question is Give an expression for the work in terms of m, v_initial, v_final ?

and i cant seem to eliminate the 's' because i end up getting

W=m*a(see above) *s and i cant get eliminate it? any ideas?
can't you use ,

[tex] v_f^2 - v_i^2 = 2as[/tex] ?
 
  • #4
11
0
the s is still in the equation though
 
  • #5
Fermat
Homework Helper
872
1
marissa12 said:
the 2nd part of the problem is w= intergral of { mv*dv} between v_final and v_initial
and we are supposed to express that in m_vinitial and v_final

and i got the answer ((m*v_final)^2-(m*v_initial)^2)/2 and that didnt work. i used the basic intergral formula

fint{t*dt between a and b} = b^2-a^2/t
[tex]\int_{vi}^{vf} mv dv = m[v^2/2]_{vi}^{vf}[/tex]

The m doesn't get squared.
 
  • #6
Fermat
Homework Helper
872
1
marissa12 said:
the s is still in the equation though
substitute for "as" from one eqn into t'other.
 
  • #7
11
0
oo thats right stupid parentheses.. but i still cant get the first part?
 
  • #8
Fermat
Homework Helper
872
1
W = Fs = Mas

vf² - vi² = 2as ==> as = ½(vf² - vi²)

So,

W = Mas = M*½(vf² - vi²)
W = (M/2)(vf² - vi²)
================
 
Last edited:
  • #9
13
0
o wow yea that makes alot more sense than what i had, i used the wrong eq. lol thank youuu!!
 

Related Threads on Solving for variables

  • Last Post
Replies
1
Views
1K
  • Last Post
Replies
2
Views
2K
Replies
8
Views
6K
Replies
2
Views
1K
Replies
1
Views
1K
Replies
2
Views
2K
Replies
1
Views
2K
Replies
12
Views
2K
Replies
1
Views
2K
Replies
8
Views
1K
Top